1996
DOI: 10.1179/cmq.1996.35.1.31
|View full text |Cite
|
Sign up to set email alerts
|

Alkali Reductive Roasting of Ilmenite Ore

Abstract: Reductive roasting of ilmenite ore by carbon in the presence of sodium carbonate was carried out at 1000-1200°C for periods of up to 180 min. Additions of sodium carbonate of up to 30 wt% of the ore enhanced the reduction efficiency. The maximum metallization obtained at 1200°C was about 85%, and the rest of the iron exists in the form of sodium-iron-titanates. The type of sodium compound formed in the final product depends on the roasting temperature. The reduction rate data under isothermal conditions were r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
18
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(23 citation statements)
references
References 8 publications
4
18
0
Order By: Relevance
“…Splitting the design, Tables 7 and 8, leads to precisely predicting the metallization at low and high factor levels and not at 1100 • C. The slope difference of the contour plots Figs. 6 and 7 confirms our previous findings that the reduction of ilmenite is a complex process and the mixed control equation (phase boundary/gaseous diffusion mechanism) was just fitting the reduction isotherm of ilmenite up to 85% reduction (El-Tawil et al, 1996). Moreover, analyzing the data into a new design at the region 1050-1150 • C, Table 9, where the significant change was expected to occur showed that the model representing the phenomenon in that region is not linear anymore.…”
Section: Splitting the Design Into Two Designssupporting
confidence: 81%
See 3 more Smart Citations
“…Splitting the design, Tables 7 and 8, leads to precisely predicting the metallization at low and high factor levels and not at 1100 • C. The slope difference of the contour plots Figs. 6 and 7 confirms our previous findings that the reduction of ilmenite is a complex process and the mixed control equation (phase boundary/gaseous diffusion mechanism) was just fitting the reduction isotherm of ilmenite up to 85% reduction (El-Tawil et al, 1996). Moreover, analyzing the data into a new design at the region 1050-1150 • C, Table 9, where the significant change was expected to occur showed that the model representing the phenomenon in that region is not linear anymore.…”
Section: Splitting the Design Into Two Designssupporting
confidence: 81%
“…The decrease in weight was employed to calculate the oxygen removed as CO which represents the extent of reduction. The experimental procedure and the reduction isotherms as well as phase compositions of samples are described elsewhere (El-Tawil et al, 1996;Grey et al, 1974).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…[5][6][7][8][9][10][11][12][13][14][15] However, study on high-Cr V-Ti magnetite has been scarce. [2,3,16] Cr 2 O 3 , a refractory oxide, affects the blast furnace reduction and slagging process; furthermore, chromium in molten iron significantly affects the follow-up converter vanadium extraction process.…”
Section: Introductionmentioning
confidence: 99%